The High Testosterone Concentrations of the Bucks Used in the “Male Effect” Is Not a Prerequisite for Obtaining High Ovarian Activity in Goats from Mediterranean Latitudes - Luis Ángel Zarazaga; María-Carolina Gatica; Ignacio De La Rosa; Manuel Delgado-Pertíñez; José Luis Guzmán (Animals, 2022)
Two experiments were carried out. Firstly, 54 anestrous females were placed in contact with photostimulated males (Photo; n = 27) or with no photostimulated males (Natural; n = 27). Moreover, a group of bucks treated with artificial photoperiod and a group of bucks subjected to natural photoperiod without contact with females was used (Photo Isolated and Natural Isolated, respectively). In the Natural groups, the testosterone concentrations were similar except for three days after the introduction of the bucks to the does (19.72 ± 4.11 vs. 2.05 ± 0.25 ng/mL for Natural and Natural isolated bucks, respectively, p < 0.05). However, no differences were observed in the Photo groups during the entire experiment. The percentage of females showing estrous was higher in the group of females in contact with photostimulated bucks (96 vs. 74%, respectively, p < 0.05). In the second experiment, a GnRH agonist, deslorelin, was used to regulate the testosterone concentrations of the bucks. Seventy anestrous females were divided into five groups depending on the treatment received by the bucks to which they were exposed: photostimulated bucks (Photo group, n = 14); photostimulated bucks but treated with the agonist at the onset of the photoperiod treatment (Photo-Ago Long group, n = 13); photostimulated bucks but treated with the agonist at the end of the photoperiod treatment (Photo-Ago Short group, n = 15); bucks receiving no photostimulation but treated with the agonist at the end of the photoperiod treatment period (Natural-Ago Short group, n = 13) and bucks receiving no photostimulation nor agonist (Natural group, n = 15). The agonist treatment increased testosterone concentrations after the injection, which remained high for the entire experiment (p < 0.05). Six days after the introduction of the bucks to the does, the testosterone concentrations increased only in the Natural group reaching similar concentrations to the other groups (12.17 ± 6.55, 16.69 ± 4.53, 8.70 ± 0.61, 11.03 ± 1.45 and 14.42 ± 3.64 ng/mL for Photo, Photo-Ago Long, Photo-Ago Short, Natural-Ago Short and Natural bucks, respectively, p > 0.05). No differences in reproductive parameters were observed (p > 0.05). These results demonstrate that, at Mediterranean latitudes, anestrous females can stimulate the testosterone concentrations of bucks after a period of isolation. The high testosterone concentrations are not a prerequisite for an adequate response to the male effect.